Bond, vibration and microwave dielectric characteristics of Zn1-x(Li0.5Bi0.5)xWO4 ceramics with low temperature sintering - Qin Zhang; Hua Su; Huaiwu Zhang; Xiaoli Tang (Journal of Materiomics, 2022)
The bond, vibration and microwave dielectric characteristics of Zn1-x (Li0.5Bi0.5)xWO4 (x = 0–0.12) ceramics were investigated by XRD refinement, Raman and FT-IR spectroscopy and complex bond valence theory. The results showed that proper substitution of (Li0.5Bi0.5)2+ can improve the sintering characteristics and microwave dielectric properties of ZnWO4. The increase of Q×f value was mainly attributed to dense and uniform microstructure, and the subsequent decrease resulted from the deterioration of structural stability and relative density. According to the complex bond valence theory, the chemical bond characteristics of ZnWO4 and Bi2WO6 played an important role in the dielectric properties of the samples. Additionally, the samples (x = 0.02) sintered at 900 °C showed satisfactory properties: εr = 15.332, Q×f = 35,762 GHz, and τf = −65 ppm/°C, making it a potential candidate material for LTCC applications.